The boy who harnessed the wind : creating currents of electricity and hope - Kamkwamba, William, 1987-; Mealer, Bryan (New York : Harper Perennial, 2010)
An enterprising teenager in Malawi builds a windmill from scraps he finds around his village and brings electricity, and a future, to his family.
"A hardcover edition of this book was published in 2009 by William Morrow"--T.p. verso.
Keywords: Kamkwamba, William, -- 1987-; Mechanical engineers -- Malawi -- Biography; Inventors -- Malawi -- Biography; Windmills -- Malawi; Water-supply, Rural -- Malawi; Rural electrification -- Malawi; Electric power production -- Malawi; Malawi -- Rural conditions